2005
DOI: 10.1111/j.1365-2354.2005.00505.x
|View full text |Cite
|
Sign up to set email alerts
|

Information and support needs of callers to the Cancer Helpline, The Cancer Council Victoria

Abstract: The broad aims of the present evaluation were, firstly, to describe the information and support needs of callers to a Cancer Helpline and, secondly, to describe the response of the service to these needs. A further aim was to use these results to develop strategies to improve the service. Anonymous caller information collected over a 6-year period was analysed. The setting of the study was the Cancer Helpline service operated by the Cancer Council Victoria within the state of Victoria, Australia. The caller pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
56
0
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 47 publications
(65 reference statements)
3
56
0
2
Order By: Relevance
“…The database also showed that during these calls some family members and friends of patients with cancer discussed issues surrounding unproven cancer-related diet and nutrition cancer (n=88), risk factors and causes (n=62), early detection (n=57), food and nutrition programs (n=41) and cancer prevention (n=29). Although previous Cancer Helpline evaluations have demonstrated that discussion topics vary by caller type, 8 this finding illustrates the potential readiness of family and friends of patients with cancer to discuss issues associated with cancer risk and lifestyle factors. This finding also positions itself within models of behaviour change, such as the Health Belief Model, 9 in that relatives of cancer patients may be receptive to health promotion messages because of their heightened sense of susceptibility to negative health consequences.…”
mentioning
confidence: 79%
“…The database also showed that during these calls some family members and friends of patients with cancer discussed issues surrounding unproven cancer-related diet and nutrition cancer (n=88), risk factors and causes (n=62), early detection (n=57), food and nutrition programs (n=41) and cancer prevention (n=29). Although previous Cancer Helpline evaluations have demonstrated that discussion topics vary by caller type, 8 this finding illustrates the potential readiness of family and friends of patients with cancer to discuss issues associated with cancer risk and lifestyle factors. This finding also positions itself within models of behaviour change, such as the Health Belief Model, 9 in that relatives of cancer patients may be receptive to health promotion messages because of their heightened sense of susceptibility to negative health consequences.…”
mentioning
confidence: 79%
“…Seventy-seven percent of the callers were women. Other reports also indicated that women made up the majority of callers to a cancer helpline [18] [23].…”
Section: Discussionmentioning
confidence: 99%
“…They are a reliable source of information for people with cancer and their caregivers, especially those who do not have internet access or who prefer talking directly to a cancer resource professional [18] [22] [24]. Similar to the internet, telephone helplines are not constrained by geographic location or transportation issues and grant a certain degree of anonymity to the caller.…”
Section: Cancer Helplinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Medical personnel may help patients manage mental stress by guiding them to release their emotions, provide emotional support, and help patients adapt to the disease (Goldman et al, 2007). A study by Jefford, Kirke et al (2005) shows that, of the 76000 telephone counseling conducted, more than 50% of the calls were made by the general public inquiring about cancer prevention and most of the questions posed by the cancer patients and their family members were related to cancer treatment and management. A retrospective study by Jeffordet al (2005) evaluated 27480 telephone counseling and found that in average, each call lasted for about 4 minutes and 70% of the calls lasted less than 7 minutes, and calls by cancer patients and their family members were usually made to inquire about cancer related matters such as cancer treatment, management of side effects, and tests and examinations.…”
Section: Relating Clinical Problems Of Cancer Patients To Tcs Intervementioning
confidence: 99%